KINERJA POLRES KENDAL DALAM MENANGANI KASUS TAWURAN PELAJAR DI KABUPATEN KENDAL - Felisha Erika Putri Nurmala; Augustin Rina Herawati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Student brawls in Kendal Regency have escalated from sporadic juvenile incidents into organised acts of collective violence involving bladed weapons and social-media-driven mobilisation, posing a tangible threat to public order and security. This study analyses the performance of the Kendal District Police (Polres Kendal) in handling student brawls and identifies the supporting and inhibiting factors affecting that performance. A descriptive qualitative method was applied with purposive and snowball sampling, involving structural officers of Polres Kendal as well as students previously implicated in brawls. Data were collected through in-depth interviews, non-participatory observation, and documentation, then analysed using the interactive model of Miles, Huberman, and Saldaña within Agus Dwiyanto's public-organisation performance framework. The study finds that police performance has been actively implemented across multiple dimensions, particularly in operational response and incident handling, through the simultaneous application of preventive, repressive, and educative measures. However, its effectiveness remains constrained, most notably in personnel capacity, territorial surveillance coverage, and the consistency of post-guidance monitoring. Conversely, the utilisation of cyber patrol technology, leadership support, and school collaboration constitute reinforcing factors, though their implementation requires further strengthening to generate more sustained impact in curbing recurring patterns of student brawls.